Handling Four DOF Robot to Move Objects Based on Color and Weight using Fuzzy Logic Control - Nugroho, Emmanuel Agung; Setiawan, Joga Dharma; Munadi, M. (Universitas Muhammadiyah Yogyakarta, 2023)
Manipulators are increasingly used in industry to improve efficiency in jobs that require precision, long duration, and repetitive work. This research was conducted on a laboratory scale to control manipulators on a pick-and-place system in the product storage and packing area. The object of this research is a four-degree-of-freedom (4-DOF) manipulator controlled using a fuzzy logic system. The hardware used is a conveyor machine to model the product delivery process, Dobot Magician as a 4-DOF manipulator, HX711 load cell serves as a weight sensor, TCS-3200 serves as a color sensor, and Arduino Mega 2560 as a controller. The software used is Dobot Studio as the main program to control the movement of the robot and Matlab to develop the Fuzzy Logic Control (FLC) function, which is embedded in the Arduino. Fuzzy logic control processes weight variables and color variables read by sensors as information data to control the movement of the manipulator. The results showed that the manipulator was able to pick up and place objects according to the path-planning coordinates. The testing data states that the precision and accuracy of the average coordinates of product pick and place against the path planning has an error deviation of 1.8%.